Team Social Exchange Relationships, Job Stress, and Intention to Leave - Setiadi Wijaya, Nikodemus Hans; Winiasih, Raden Roro Ermetta (International Journal of Psychosocial Rehabilitation, 2020)
Employee well-being and happiness at work become significant factors for retaining them to continue working in an organization. Drawing on well-being theory, this research investigates the effects of team exchange relationships that consists of leader-member exchange (LMX) and team-member exchange (TMX) on job stress and intention to leave. A total of 172 samples were taken from employees of the Adisutjipto International Airport in Yogyakarta, Indonesia. LMX and TMX had negative effects on intention to leave and job stress, job stress had a positive effect on intention to leave. The LMX-intention to leave and TMX-intention to leave relationships were mediated by job stress. The study discloses how the both exchange relationships may attenuate employee stress